Propose Measures for Enhancement: Multiple Intelligence Based Instructional Strategies - Esmeralda, Angel II P. (MID Publisher International, 2024)
This study explores the effectiveness of multiple intelligence-based instructional strategies in enhancing the learning experiences and development of secondary high school students. Rooted in Howard Gardner’s theory of multiple intelligences, the research aims to identify how various teaching approaches can cater to diverse learner profiles, including mastery, interpersonal, understanding, and self-expressive styles. The study also investigates the impact of these strategies on developing students’ logical-mathematical, verbal-linguistic, and spatial intelligences. Utilizing a descriptive research design, data were collected from teachers at the International Bureau of Management through questionnaires and analyzed using mean scores and weighted averages. Findings reveal that instructional strategies aligned with multiple intelligences significantly contribute to students’ cognitive, affective, and psychomotor development. Mastery and interpersonal teaching styles were particularly effective in fostering engagement and comprehension, while self-expressive approaches promoted creativity and personal insight. Despite the overall positive outcomes, challenges such as managing classroom behavior and facilitating critical thinking were identified as obstacles to optimal intelligence development. The study recommends that educators integrate diverse instructional methods tailored to multiple intelligences and continuously refine their teaching practices to address these challenges. Ultimately, adopting multiple intelligence-based strategies promotes holistic learning, enabling students to realize their full potential across varied intellectual domains.